NEST REUSE AND COMMUNAL NESTING IN MICROTHURGE-CORUMBAE (HYMENOPTERA, MEGACHILIDAE), WITH SPECIAL REFERENCE TO NEST DEFENSE - Garofalo, C. A.; Camillo, E.; Campos, MJO; Serrano, J. C. (Birkhauser Verlag Ag, 1992)
Observations on the nesting activities of Microthurge corumbae, carried out at the University Campus of Ribeirao Preto, São Paulo, Brazil, from 1977 to 1981, indicated that 61.9% of nests were re-used by succeeding generations. Re-use by one generation was more frequent than by two generations, and re-use by a third was observed only once. Nests were re-used by one or several females. Single females were more frequently in the first re-use. In these cases nest re-use did not differ essentially from the solitary foundation of a new nest, except for the adoption of a pre-existing nest without excavation. In multifemale nests, analysis of relative age (wing wear), ovarian and spermathecal conditions of associated females and the content of nests at excavation indicated that the social pattern in such colonies is communal. There is some evidence that the associated females are relatives. The chalcidoid wasp Leucospis was the principal nest parasite, and ants of the genus Crematogaster were nest predators. In multifemale nests, the rate of parasitism was significantly lower than in solitary nests, indicating that nest-sharing resulted in improved nest defense. on the other hand. The absence of predation on immatures of the first generation of M. corumbue in multifemale nests suggests that such nests are also more resistant to attack by predators.
Keywords: NEST REUSE; COMMUNAL NESTING; NEST DEFENSE; MICROTHURGE-CORUMBAE; MEGACHILIDAE